Efficient and Adaptively Secure Attribute-Based Proxy Reencryption Scheme. (25th May 2016) - Li, Huixian; Pang, Liaojun
Abstract : Ciphertext-Policy Attribute-Based Proxy Reencryption (CP-ABPRE) has found many practical applications in the real world, because it extends the traditional Proxy Reencryption (PRE) and allows a semitrusted proxy to transform a ciphertext under an access policy to the one with the same plaintext under another access policy. The existing CP-ABPRE schemes were proven secure only in the selective security model, a limited model, which is an unnatural constraint on the attacker. The scheme proved in this model can only be called selectively secure one. However, from a security perspective, the adaptively secure CP-ABPRE scheme is more desirable. In this paper, an adaptively secure CP-ABPRE scheme is proposed, which is based on Waters' dual system encryption technology. The proposed scheme is constructed in composite order bilinear groups and proven secure under the complexity assumptions of the subgroup decision problem for 3 primes (3P-SDP). Analyses show that our proposal provides higher computational efficiency compared with the existing schemes.